Ethno-medicinal Study of some Important Plants of Jharkhand and their Conservation - Vidhyarthy, Anil Kumar; Gupta, H. S. (Indian Forester, 2004)
The increasing demand of medicinal plants has resulted in the rapid dwindling of these natural resources and there is a urgent need of systematic and conservation and sustainable production of medicinal plants involving local communities, university students and developmental field groups with stronger linkages for collaborative work to meet future demand on a sustained manner. There are some plants which are a panacea for most human ailments. Their documentation is the need of the hour. Also suitable propagation techniques are to be developed, like tissue culture etc. In light of this, it is essential to havc an interface between traditional trends and modern concept of production, marketing and technology of this important resource. Creating awareness and proper networking on the medicinal properties of these indigenous plants, which we very often encounter in our daily life, through dissemination of research data with extension activities will go a long way in conserving nature’s priceless gift.